Diamidophosphines with six-membered chelates and their coordination chemistry with group 4 metals: development of a trimethylene-methane-tethered [PN2]-type "molecular claw". Issue 8 (25th January 2016) - Batke, S.; Kothe, T.; Haas, M.; Wadepohl, H.; Ballmann, J.
Abstract : Group 4 complexes bearing novel diamidophosphines with the metals embedded in six-membered chelates were explored and a new tripodal trimethylene-methane-tethered diamidophosphine was developed. Abstract : The coordination chemistry of the phosphine-tethered diamidophosphine ligands PhP(CH2 CH2 CH2 NHPh)2 ( pr [NPN]H2 ) and PhP(1, 2-CH2 -C6 H4 -NHSiMe3 )2 ( bn [NPN]H2 ) featuring six-membered N–C3 –P chelates was explored with group 4 metals, which allowed for the consecutive development of a new trimethylene-methane-tethered [PN2 ] scaffold. In the case of the propylene-linked system pr [NPN]H2, access to the sparingly soluble dibenzyl derivative pr [NPN]ZrBn2 (3-Zr ) was gained, while thermally sensitive zirconium and hafnium diiodo complexes bn [NPN]MI2 (5-M, M = Zr, Hf) were isolated in the case of the benzylene-linked derivative bn [NPN]H2 . Despite the related phosphine-tethered backbone architectures of both of these ligands, their group 4 complexes were found to exhibit either C 1 -symmetric ( bn [NPN]MX2 ) or averaged C S -symmetric ( pr [NPN]MX2 ) structures in solution. To restrain the overall flexibility of these systems and thereby control the properties of the resulting complexes without disrupting the six-membered chelates, the new trimethylene-methane-tethered N, N ′-di-( tert -butyl)-substituted [PN2 ]H2 protioligand was designed. This tripodal ligand system was prepared on a gram scale and its C S -symmetric dichloro complexes [PN2 ]MCl2 (6-M, M = Ti, Zr, Hf) were isolated subsequently. The benzene-soluble dibenzyl derivative [PN2 ]ZrBn2 (7-Zr ) was synthesised as well and characterised by X-ray diffraction. These results are discussed not only in conjunction with the known [NPN]-coordinated group 4 complexes incorporating five-membered chelates, but also in the context of "molecular claws" that are related to the new [PN2 ] tripod.